Modeling of fluorocarbon films deposition by HFCVD - Jarusiripot, Chutima, author; Dandy, David S., advisor; Belfiore, Laurence A., committee member; Fisher, Ellen R., committee member; Parkinson, Bruce A., committee member; Sampath, Walajabad S., committee member (Colorado State University. Libraries, 2006)
The present studies are directed toward the design of a new, one-dimensional, continuous flow HFCVD reactor using a rigorous computational fluid dynamics (CFD) approach. The uniform concentration boundary layer thickness over the substrate is required to achieve good quality films. First the inlet showerhead is simulated to determine the appropriate velocity profile for the reactor design simulations. The effects of the spacing between holes in the inlet showerhead, space near the walls, and the diameter of the showerhead holes have been investigated. The results from these studies indicate that there is little effect on the entrance length and the shape of the velocity profiles due to the shower hole spacing, shower hole diameter, and spacing near the chamber walls. The velocity profiles derived from Navier Stokes equation for a rectangular chamber showed very good agreement with the simulation profiles. This analytical expression was applied as the inlet velocity boundary condition gas flow. Next, the effects of the filament diameter and the spacing between filaments on the temperature distribution in the gas above the substrate region were investigated. Only the momentum and energy conservation equations were used in the calculations. The results show that the filament diameter and the spacing between each filament are also crucial to the temperature profiles. Increasing the filament spacing and filament diameter increases temperature fluctuations. Next, the effects of gas flow rate, hot gas volume thickness, the space above the filaments, and the space between the substrate and hot gas on the temperature and mass fraction profiles were investigated using the reactor with the surrogate filament array. By changing the reactor flow rate in the range of 0.001 to 0.1 m3/s (which is equivalent to the Reynolds number of 2.75 to 275) significantly changed both the temperature and mass fraction profiles. Uniform temperature achieved when the flow rate was at least 0.01 m3/s. The CF2 mass fraction gradient near the substrate surface is highest and more uniform in the flow direction when the flow rate is approximately 0.01 m3/s. Increasing the hot gas region thickness does not change the temperature profile below the filaments, but increases the extent of the reaction in the reactor, resulting in a higher CF2 gradient near the substrate. When the space above the filament array was reduced from 1.65 cm to 0.5 cm, the temperature profiles below the filament arrays was not changed, however the CF2 mass fraction gradient near the substrate was increased. Decreasing the space below the filament from 6.5 to 5 mm does not significantly Change either the temperature or CF2 mass fraction profiles near the substrate. The optimal range is somewhere between 5 to 7 mm.
Keywords: chemical engineering